P242 Demographics and clinical characteristics of patients with COPD utilizing LAMA/LABA fixed-dose combination therapy: a U.S. database study. (December 2018) - Ding, B; Kallenbach, L; Slipski, L; Wilk, A; O'Brien, D; Guranlioglu, D
Abstract : Introduction and objectives: To characterize patients with chronic obstructive pulmonary disease (COPD) who were prescribed long-acting muscarinic antagonist/long-acting β2 -agonist (LAMA/LABA) fixed-dose combination (FDC) therapy in real-world US-based clinical practice. Methods: This retrospective cohort study of patients aged ≥40 years used data from the Practice Fusion electronic health records (EHR) database. Patients with ≥1 LAMA/LABA FDC prescription in the intake period (1 May 2014 to 31 December 2017) were included. Patients were required to have ≥1 recorded visit between ≥12 months and ≤24 months prior to the index date (defined as the date of initiating LAMA/LABA FDC) and ≥1 recorded visit ≥3 months post-index date for a 15 month assessment period. Collected data included patient demographics, COPD therapy and medication use. Results: Of 1, 258, 889 eligible patients, 19 926 initiated LAMA/LABA FDC therapy and 8224 were included in the analysis. Overall, 52.8% of patients were female, with a mean ±standard deviation age of 67.9±10.7 years, body mass index (continuous) of 29.2±7.6 kg/m 2 and a Charlson comorbidity index of 2.5±1.9. Of these, 35.9%, 42.4% and 12.9% patients were current, former and never smokers, respectively (8.8% not reported). Insurance status was reported for 48.7% of patients, of whom 25.2%, 7.1% and 29.6% had Medicare, Medicaid and commercial/other insurance, respectively. Comorbidities of cardiovascular disease, hypertension, hyperlipidaemia, type II diabetes and depression were present in 74.3%, 64.0%, 45.6%, 28.1% and 22.6% of patients, respectively. In total, 53.0% of patients in the overall cohort used inhaled medication in the 365 days pre-index period. Among these, 75.8% of patients used a short-acting bronchodilator with/without maintenance treatment, 70.3% of which was with a pressurized metered-dose inhaler (pMDI) device, and 24.2% of patients used maintenance-only therapy, 26.6% of which was with a pMDI device (table 1). Thus, 59.8% of inhaled treatment users experienced using a pMDI in the year prior to initiation of LAMA/LABA FDC therapy. Conclusions: In real-world practice, patients prescribed LAMA/LABA FDCs are generally elderly and overweight, with high comorbidities of cardiovascular disease, hypertension and hyperlipidaemia, in line with well-known COPD patient characteristics. Experience and familiarity with a pMDI were common prior to initiation of LAMA/LABA FDC therapy among patients prescribed bronchodilator therapies.